Yellow fever in plain sight: assessing disease surveillance officers’ knowledge and self-efficacy in identification and reporting in Kwara State, Nigeria - Oladayo D. Awoyale; Magbagbeola D. Dairo; Adeniyi F. Fagbamigbe; Simiat Adeogun; Oluwatosin E. Fakayode; Olufunmilayo Fawole (BMC Public Health)
Abstract Introduction Yellow fever (YF) poses a significant threat to public health in Nigeria, which bears the highest burden of the disease. Timely identification and reporting by disease surveillance officers are critical in preventing and controlling outbreaks. This study aimed to investigate the knowledge and self-efficacy of disease surveillance officers in identifying and reporting yellow fever cases in Kwara State, Nigeria. Methods A cross-sectional survey of 177 disease surveillance officers, was conducted in Kwara State, Nigeria, between June 2023 and December 2023. A pre-tested structured questionnaire was used for data collection. Data analysis was performed using Microsoft Excel 365 and SPSS 20. Results The study revealed that 82.5% of respondents demonstrated good knowledge of yellow fever, while 99.4% showed good self-efficacy in detecting and reporting cases. However, gaps in knowledge and practice were identified, particularly regarding the mode of transmission and epidemic threshold. Continuous training, retraining and regular updates on yellow fever epidemiology, transmission dynamics, and control measures should be provided to disease surveillance officers. Conclusion This study highlights the need for targeted interventions to enhance healthcare workers' knowledge and practice gaps in yellow fever identification and reporting in Kwara State, Nigeria. Continuous training and updates are crucial to ensure timely and effective response to yellow fever outbreaks, ultimately reducing the disease burden in Nigeria.